A convergência midiática e editorial no jornalismo móvel : uma análise do The Daily - Nunes, Ana Cecília Bisso (2013)
The Daily was the first publication of its kind exclusive for tablets. By its experience, we address convergence on journalism, through two main discussions: media convergence in the same journalistic publication, and editorial convergence, treated here as a mixture of popular and quality press. For that, we combine theoretical perspectives from culturalism and from Cultural Studies to problematize questions from the convergence culture (JENKINS, 2009), using the perspective of technology as effect (WILLIAMS, 2005) and the media language in the sphere of mediations (MARTÍN-BARBERO). The complexity of the comprised questions was addressed through an analysis of the product itself, qualitative interviews and the investigation of spontaneous comments about The Daily on the App Store. According to what was researched, it is proposed the configuration of a hybrid journalism in a convergent medium, perhaps in a context where the dichotomous classification between popular and quality press doesn t make sense anymore in a landscape of hybrid cultures (CANCLINI, 2003). Furthermore, we perceive that the media convergence of The Daily is still in an experimental, transitional sphere, without completeness. With the appearance of mobile technologies, digital journalism also started to aggregate mobility, bringing peculiarities and issues that may form even a new phase of digital journalism. The Daily has ceased its activities on December 15th and brought contributions to the study of convergence in journalism.